THE EFFECTIVENESS OF THE GREEN-BASED BARTENDING LEARNING IN IMPROVING THE COMPETENCE OF THE STUDENTS OF HOSPITALITY STUDY PROGRAM - I Made Darma Oka; I Nyoman Winia; I Wayan Pugra; Ni Gst Nym Suci Murni (Journal of Applied Sciences in Travel and Hospitality, 2020)
To design green-based learning, the lecturers should have broad insights on the linkages of green concepts in learning, high creativity, good learning methodology skills, high self-confidence, and courage to manage and develop materials. The formulation of the problem focused in this article is the effectiveness of green bartending learning in improving the competence of the students on Study Program of Hospitality of State Polytechnic of Bali (Politeknik Negeri Bali-PNB). This study was conducted on the fourth semester students as the research sample. The sample of research is determined according to the number of students in each class that is as much as 28 people. Based on the results of the analysis can be concluded that the application of learning based on green Bartending very effective in improving the achievement of student competencies This is evidenced by the results of statistical tests that show that there are differences in achievement of competence significantly between groups of students who are given the treatment of green-based Bartending learning with groups of students with learning using textbook/handout. It is suggested to the management to encourage and facilitate lecturers in implementing green-based learning.